Invitation to Syriac Christianity: an anthology - Penn, Michael Philip; Johnson, Scott Fitzgerald; Shepardson, Christine; Stang, Charles M. (University of California Press, 2022)
"Over the last few decades, one of the biggest growth areas in ancient history has been Syriac studies. The lingua franca of the late ancient Middle East,Syriac--the language of Syria--was native to a broad population who developed distinctive and influential form of Christianity that spread across continents, connecting the Roman, Persian, Arab, Chinese, and South Asian empires. Given this tremendous geographical spread, and the massive corpus of writings still extant, Syriac studies is increasingly felt to be central to the study of Late Antiquity. Indeed, PhDs trained in Syriac or Arabic as well Greek and Latin are the most desirable candidates on the job market today. As more and more professors are trained in these materials--and as the call grows ever louder for classes aimed at understanding the interconnectedness of premodern societies--the more Syriac becomes central to teaching in colleges and universities, as well as divinity schools and seminaries. Collecting the most important texts from the second to the fourteenth centuries, Invitation to Syriac Christianity will provide the first-ever comprehensive introduction written for the nonspecialist. These carefully selected, introduced, and annotated translations will help professors and students at all levels to expand their knowledge of the ancient world beyond Greek and Latin traditions. Invitation will thus be the essential resource for anyone wanting to study the world of Syriac"--